Public Service innovations through the establishment of the Makassar City Ombudsman (OKM) institution - Oky Nur Pratiwi Johansyah; Asri Nur Aina; Sulmiah Sulmiah; Kemal Sandi; Dewi Walahe (Program Pascasarjana Universitas Negeri Makassar, 2023)
The purpose of this study is to analyze the types of Makassar City Government Public Service innovations through the establishment of the Makassar City Ombudsman (OKM) institution. This study uses research with a qualitative method approach. The key informants in this study were the Chairperson of the Makassar City Ombudsman (OKM), the Mayor of Makassar as the leader of the Regional Apparatus Organization (OPD) of the Makassar City Government, related OPDs who directly carry out public services directly to the community, the Community as service recipients and information providers to OKM, Members DPRD Makassar Commission A. The results of the study show that the innovations carried out by the Makassar City Government through the Establishment of the Makassar City Ombudsman, by looking at 3 types of innovation in the public sector through the establishment of OKM namely, and these innovations fall into 3 types, namely (1) Radical innovation, (2) Top down innovation to bottom up innovation and (3) Needs led Innovation and efficiency-led innovation.